PENGEMBANGAN MODUL MATERI KEANEKARAGAMAN HAYATI UNTUKSMA MELALUI MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION BERBASIS QR CODE - Ari Purnama Sari; Handoko Santoso; Agil Lepiyanto (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2023)
The aims of this module development research is to be able to produce aproduct in the form of a module that uses a QR Code-based problem-basedinstruction learning model. This development research uses the 4Ddevelopment type which has 4 stages, namely define, design, develop,dessiminate. Development only does up to the develop stage. The productsdeveloped in this development are modules, the modules have passed the expertdesign validation stage with results of 82.5% with